Femoral head prosthesis adaptive to multi-taper femoral stem revision
By using polyether etherketone and composite filler in femoral head prosthesis, the problem of insufficient mechanical properties, antibacterial properties and tribological properties of femoral head prosthesis in the prior art is solved, and higher mechanical properties and antibacterial properties are achieved. Extends the service life of the prosthesis.
Patent Information
- Application Number
- CN202411661366.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polyether ether ketone-based femoral head prosthesis has shortcomings in terms of mechanical properties, antibacterial properties and tribological properties, which affects its service life.
Compound fillers are prepared by using polyether etherketone as the main matrix in the femoral head prosthesis, adding amyopted basalt fibers and acid chloride nanotitanium dioxide, to improve their compressive strength, hardness, tensile strength, wear resistance and antibacterial properties.
The excellent compressive strength, hardness, tensile strength, wear resistance and antibacterial properties of the femoral head prosthesis are achieved, and the service life of the prosthesis is extended.
Smart Images

Figure CN119455102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of femoral head prostheses, and in particular relates to a femoral head prosthesis adapted for multi-taper femoral stem revision. Background Art
[0002] In hip replacement surgery, the femoral head prosthesis is usually made of metal, ceramic or polymer materials. It is designed to match the acetabulum prosthesis to replace the diseased or damaged femoral head. In hip replacement surgery, the diseased femoral head is removed and then replaced by the femoral head prosthesis to restore the normal function of the hip joint. The femoral stem prosthesis is a long metal or ceramic component that is inserted into the medullary cavity of the femur to replace the diseased or damaged part of the femur. The femoral stem prosthesis is usually designed to match the femoral head prosthesis and is fixed to the femur by bone cement, press fit or biological fixation.
[0003] In order to achieve better treatment effects, it is necessary to improve the bioactivity of the femoral head prosthesis so that the bone tissue can be better integrated. Among them, the bioactivity, antibacterial properties, elastic modulus and other properties of the femoral head prosthesis material will be related to its compatibility with the bone tissue. Compared with metal and ceramic materials, polyetheretherketone has good mechanical properties and an elastic modulus comparable to that of human bones, and can effectively avoid the stress shielding effect produced in the later stage of prosthesis transplantation, making it widely used in bone and joint prosthesis implantation. The ideal femoral head prosthesis material needs to have excellent mechanical properties and wear resistance as well as good antibacterial properties. However, the mechanical properties, antibacterial properties and tribological properties of polyetheretherketone in the human environment need to be improved, which affects the service life of the prosthesis material. Summary of the invention
[0004] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a femoral head prosthesis suitable for multi-taper femoral stem revision, using polyetheretherketone as the main matrix and adding composite fillers to prepare a femoral head prosthesis with excellent compressive strength, hardness, tensile strength, wear resistance and antibacterial properties.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A femoral head prosthesis adapted for multi-taper femoral stem revision comprises a femoral head prosthesis, wherein the femoral head prosthesis comprises the following raw materials in parts by weight: 40-70 parts of polyetheretherketone and 10-25 parts of composite filler; the composite filler is amination basalt fiber grafted with acyl chloride nano-titanium dioxide, and the amination basalt fiber is basalt fiber grafted with 2-bromoethylamine hydrobromide.
[0006] Preferably, the method for preparing the composite filler comprises the following steps: A. Disperse the pretreated basalt fiber in deionized water, add sodium hydroxide solution, stir and mix at room temperature, then add 2-bromoethylamine hydrobromide solution and stir to react for 3-5 hours. After the reaction is completed, wash with deionized water to prepare amino basalt fiber; B. Take nano titanium dioxide and add deionized water, disperse by ultrasonic at room temperature, add sodium chloroacetate and drop sodium hydroxide solution to adjust the pH to 11-13, heat in an oil bath at 100-120° C. for 3-5 hours, cool to room temperature and wash to neutrality, then centrifuge and dry to prepare carboxylated nano titanium dioxide; C. Take carboxylated nano-titanium dioxide and add thionyl chloride, add N,N-dimethylformamide after ultrasonic oscillation, place in an 80-95°C oil bath and stir to react for 18-26 hours, filter, wash and dry to prepare acyl chloride nano-titanium dioxide; D. Take acyl chloride nano-titanium dioxide and add tetrahydrofuran solvent. After ultrasonic dispersion, add amino basalt fiber and triethylamine, stir and mix evenly, place in a 10-30°C water bath and stir to react for 12-24 hours. After the reaction is completed, centrifuge, wash and dry to prepare a composite filler.
[0007] Preferably, the specific preparation method of the pretreated basalt fiber in step A is: soak the basalt fiber in an acetone solution for 10 to 12 hours, take it out and filter it dry, then put the basalt fiber into a container filled with deionized water to soak and wash, repeat the process for multiple times, filter it out, and then dry it in an oven to prepare the pretreated basalt fiber.
[0008] Preferably, the concentration of the sodium hydroxide solution in step A is 1.5-2 g / mL.
[0009] Preferably, in step A, the addition ratio of the pretreated basalt fiber, deionized water, sodium hydroxide solution and 2-bromoethylamine hydrobromide solution is 0.2 g: 10-20 mL: 10-20 mL: 15-50 mL.
[0010] Preferably, in step B, the mass ratio of nano titanium dioxide to sodium chloroacetate is 1:1.2-1.5.
[0011] Preferably, in step C, the addition ratio of carboxylated nano-titanium dioxide and thionyl chloride is 1 g: 60-90 mL.
[0012] Preferably, in step D, the mass ratio of the acyl chloride nano-titanium dioxide, the amination basalt fiber and the triethylamine is 1:0.6-2:0.02-0.15.
[0013] Preferably, the femoral head prosthesis for multi-taper femoral stem revision as described above is prepared by the following method: polyetheretherketone and composite filler are weighed in parts by weight, pre-mixed in a high-speed mixer, and then mixed, extruded, granulated and molded using a twin-screw extruder at 280-365°C to prepare the femoral head prosthesis.
[0014] Beneficial effects of the present invention: The present invention uses polyetheretherketone as the main matrix and adds composite fillers to prepare a femoral head prosthesis with excellent compressive strength, hardness, tensile strength, wear resistance and antibacterial properties. The present invention uses a nucleophilic substitution reaction to in-situ graft 2-bromoethylamine hydrobromide onto the surface of basalt fiber to prepare amination basalt fiber. In addition, the present invention heats nano-titanium dioxide and sodium chloroacetate under alkaline conditions to prepare carboxylated nano-titanium dioxide, reacts the obtained carboxylated nano-titanium dioxide with thionyl chloride, introduces acyl chloride groups on the surface of nano-titanium dioxide, and then reacts with amino groups on the surface of amination basalt fiber to graft nano-titanium dioxide onto the surface of basalt fiber to prepare composite fillers. Among them, basalt fiber is a high-performance fiber material with high elastic modulus, high tensile strength, high wear resistance, excellent high temperature resistance and acid and alkali resistance. However, the surface of basalt fiber carries negative charge and lacks cell binding sites. Since the cell membrane surface is negatively charged, the adhesion of cells on the surface of basalt fiber is hindered. In the present invention, 2-bromoethylamine hydrobromide is grafted on the surface of basalt fiber to make the surface of basalt fiber carry positive charge. The positively charged amino group can contact with the negatively charged bacterial cell membrane through electrostatic interaction, thereby destroying the cell membrane. The stability and integrity of the basalt fiber can effectively inhibit the growth and reproduction of bacteria. At the same time, nano-titanium dioxide, as an inorganic antibacterial agent, has good biocompatibility and broad-spectrum antibacterial function, can inhibit and kill microorganisms, and has deodorizing and mildew-proof effects. Under the action of chemical bonds, the basalt fiber and nano-titanium dioxide are tightly combined, which is conducive to the dispersion of nano-titanium dioxide. At the same time, the presence of nanoparticles increases the roughness of the basalt fiber surface, increases the mechanical bite force and chemical bonding force between the basalt fiber and the matrix, and improves the interface bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The present invention will be further described below in conjunction with the accompanying drawings.
[0016] Figure 1 It is a schematic diagram of the overall structure of the femoral head prosthesis of the present invention.
[0017] Figure 2 It is a schematic diagram of the cross-sectional structure of the femoral head prosthesis of the present invention.
[0018] Figure 3 It is a schematic diagram of the femoral head prosthesis and the conical structure of the head of the present invention.
[0019] Figure 4 It is a schematic diagram of the limiting groove structure of the present invention.
[0020] Figure 5 This is a diagram showing the matching of the through hole and the ball of the present invention.
[0021] The figure shows: 1. Femoral head prosthesis; 2. Head cone; 3. Bearing tube; 4. Ball; 5. Mounting cavity; 6. Through hole; 7. Spring; 8. Bump; 9. Medical sealant; 10. Arc surface; 11. Groove; 12. Limiting groove. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The basalt fibers in the embodiments and comparative examples of the present invention are produced by Shenzhen Teli New Material Technology Co., Ltd. and have a length of 3 mm and a diameter of 13 μm.
[0024] Embodiment 1 A method for preparing a composite filler comprises the following steps: A. Take 0.2g of pretreated basalt fiber and disperse it in 20mL of deionized water, add 20mL of 1.5g / mL sodium hydroxide solution, stir and mix at room temperature, then add 30mL of 2-bromoethylamine hydrobromide solution and stir to react for 4h. After the reaction is completed, wash with deionized water to prepare amino basalt fiber; B. Take 1g of nano titanium dioxide and add 300mL of deionized water, disperse by ultrasonic at room temperature, add 1.5g of sodium chloroacetate and dropwise add 0.1mol / L sodium hydroxide solution to adjust the pH to 12, heat in an oil bath at 120°C for 5h, cool to room temperature and wash to neutrality, then centrifuge and dry to prepare carboxylated nano titanium dioxide; C. Take 1g of carboxylated nano-titanium dioxide and add 60mL of thionyl chloride. After ultrasonic oscillation, add N,N-dimethylformamide, place in a 90°C oil bath and stir for 24h. After filtering, washing and drying, acyl chloride nano-titanium dioxide is prepared. D. Take 1g of acyl chloride nano-titanium dioxide and add it into 20mL of tetrahydrofuran solvent. After ultrasonic dispersion, add 1.5g of amino basalt fiber and 0.05g of triethylamine. Stir and mix evenly. Place in a 10℃ water bath and stir to react for 24h. After the reaction is completed, centrifuge, wash and dry to prepare a composite filler.
[0025] The specific preparation method of the pretreated basalt fiber is as follows: soak the basalt fiber in an acetone solution for 10 hours, take it out and filter it, then put the basalt fiber into a container filled with deionized water to soak and wash, repeat the process for several times, filter it out, and then dry it in an oven to prepare the pretreated basalt fiber.
[0026] Embodiment 2 A femoral head prosthesis adapted for multi-taper femoral stem revision, comprising a femoral head prosthesis 1, a mounting cavity 5 is provided in the femoral head prosthesis 1, and the mounting cavity 5 is inverted cone shape, a bearing cylinder 3 in the shape of an inverted cone is slidably provided in the mounting cavity 5, and there is a gap between the mounting cavity 5 and the bearing cylinder 3, and the gap diameter increases upward along the axial direction of the femoral head prosthesis 1, six through holes 6 are provided on the conical surface of the bearing cylinder 3, and the six through holes 6 are arranged in a circle, and a ball 4 is slidably installed in each through hole 6, and the ball 4 is fitted with the mounting cavity 5, the bearing cylinder 3 is plugged into the head cone 2, and the head cone 2 is provided with a useful On the arc surface 10 connected to the conical neck, the upper bottom surface of the supporting tube 3 is connected to the installation cavity 5 through the spring 7. When the head cone 2 is inserted into the supporting tube 3, the conical surface of the head cone 2 abuts against the ball 4. The ball 4 is squeezed and slides in the through hole 6 along the installation cavity 5, and drives the supporting tube 3 to move upward. The gap continues to increase, and the head cone 2 is completely inserted into the supporting tube 3. The gap is in the maximum state. The spring 7 pushes the supporting tube 3 to reset, so that the ball 4 slides from the edge of the head cone 2. At this time, the arc surface 10 abuts against the installation cavity 5 through the ball 4, and the head cone 2 is in a completely fixed state.
[0027] Six limiting grooves 12 are provided on the inner wall of the installation cavity 5, and each limiting groove 12 is slidably connected to the ball 4. A protrusion 8 is fixedly connected to the upper bottom surface of the installation cavity 5. When the head cone 2 is fully inserted into the bearing cylinder 3, the head cone 2 abuts against the protrusion 8. The contact point between the ball 4 and the through hole 6 is located between the axis of the bearing cylinder 3 and the axis of the ball 4. A groove 11 is provided in the installation cavity 5, and a medical sealant 9 is arranged in the groove 11. The diameter of the groove 11 is larger than the diameter of the lower bottom surface of the bearing cylinder 3.
[0028] The femoral head prosthesis 1 comprises the following raw materials in parts by weight: 40 parts of polyetheretherketone and 12 parts of composite filler.
[0029] The preparation method of the femoral head prosthesis for multi-taper femoral stem revision is as follows: polyetheretherketone and composite filler are weighed by weight, premixed in a high-speed mixer, and then mixed, extruded, granulated and molded at 300°C using a twin-screw extruder to prepare the femoral head prosthesis.
[0030] Embodiment 3 A femoral head prosthesis adapted for multi-taper femoral stem revision comprises a femoral head prosthesis 1. The femoral head prosthesis comprises the following raw materials in parts by weight: 55 parts of polyetheretherketone and 19 parts of composite filler.
[0031] The preparation method of the femoral head prosthesis adapted for multi-taper femoral stem revision is the same as that in Example 2.
[0032] Embodiment 4 A femoral head prosthesis adapted for multi-taper femoral stem revision comprises a femoral head prosthesis 1. The femoral head prosthesis comprises the following raw materials in parts by weight: 70 parts of polyetheretherketone and 23 parts of composite filler.
[0033] The preparation method of the femoral head prosthesis adapted for multi-taper femoral stem revision is the same as that in Example 2.
[0034] Comparative Example 1 A femoral head prosthesis adapted for multi-taper femoral stem revision includes a femoral head prosthesis 1. The femoral head prosthesis includes the following raw materials in parts by weight: 57 parts of polyetheretherketone, 8 parts of pretreated basalt fiber, and 10 parts of nano-titanium dioxide.
[0035] The preparation method of the femoral head prosthesis adapted for multi-taper femoral stem revision is the same as that in Example 2.
[0036] Comparative Example 2 A femoral head prosthesis adapted for multi-taper femoral stem revision includes a femoral head prosthesis 1. The femoral head prosthesis includes the following raw materials in parts by weight: 60 parts of polyetheretherketone and 12 parts of amino basalt fiber.
[0037] The preparation method of the femoral head prosthesis adapted for multi-taper femoral stem revision is the same as that in Example 2.
[0038] Comparative Example 3 A femoral head prosthesis adapted for multi-taper femoral stem revision includes a femoral head prosthesis 1. The femoral head prosthesis includes the following raw materials in parts by weight: 65 parts of polyetheretherketone and 20 parts of nano-titanium dioxide.
[0039] The preparation method of the femoral head prosthesis adapted for multi-taper femoral stem revision is the same as that in Example 2.
[0040] Performance Testing (1) Compressive strength test: The femoral head prostheses prepared in Examples 2-4 and Comparative Examples 1-3 were injection molded into specimens using an injection molding machine. A universal testing machine was used for compression testing at a rate of 5 mm / min. The test results are shown in Table 1.
[0041] (2) Hardness test: The femoral head prostheses prepared in Examples 2-4 and Comparative Examples 1-3 were injection molded into test specimens using an injection molding machine. A Shore hardness tester was used to perform a surface hardness test. The test results are shown in Table 1.
[0042] (3) Tensile strength test: The femoral head prostheses prepared in Examples 2-4 and Comparative Examples 1-3 were injection molded into specimens using an injection molding machine. A universal testing machine was used to perform a tensile test according to ASTM-D3039. The tensile speed was 2 mm / min. The tensile strength was calculated according to the formula: T = Ft / A, where Ft represents the tensile force when the sample breaks (N), and A is the fracture surface area of the sample (mm 2 ), and the test results are shown in Table 1.
[0043] (4) Wear test: The femoral head prosthesis prepared in Examples 2-4 and Comparative Examples 1-3 was processed into a semi-cylinder with a radius of 10 mm as the upper test sample, and XLPE was processed into a disc with a diameter and thickness of 20 mm and 4 mm, respectively, as the lower test sample. A multifunctional friction and wear testing machine was used to perform reciprocating friction. First, the upper and lower samples were cleaned with ultrapure water, and then placed in an oven at 60°C for 24 hours. After cooling, the masses of the upper and lower samples were weighed. After rubbing for 30 minutes using the multifunctional friction and wear testing machine, the upper and lower samples were ultrasonically cleaned three times with anhydrous ethanol solution, and then placed in an oven at 60°C for 24 hours. After cooling, they were weighed. The test results are shown in Table 1.
[0044] Table 1 Sample performance test results
[0045] From the data results in Table 1, it can be seen that the femoral head prostheses prepared in Examples 2-4 of the present invention have better compressive strength, hardness, tensile strength and wear resistance than those in Comparative Examples 1-3, indicating that the addition of basalt fiber and nano-titanium dioxide and the grafting of the two can enhance the mechanical properties and wear resistance of the samples.
[0046] (5) Antibacterial performance test: The femoral head prostheses prepared in Examples 2-4 and Comparative Examples 1-3 were molded into test specimens by an injection molding machine. Two common pathogenic bacteria of the human body, Escherichia coli and Staphylococcus aureus, were selected for testing. According to the plate coating method, 100 uL of the solution with a concentration of 1×10 6 The bacterial solution of CFU / L was evenly spread on the agar medium, and then the sample was placed on the medium coated with the bacterial solution and cultured in a constant temperature incubator at 37°C for 24 hours. The antibacterial effect of the sample was judged by observing the diameter of the inhibition zone. The test results are shown in Table 2.
[0047] Table 2 Antibacterial performance test results
[0048] It can be seen from the data results in Table 2 that the femoral head prosthesis prepared in Examples 2-4 of the present invention has better antibacterial properties than Comparative Examples 1-3. Wherein 2-bromoethylamine hydrobromide is not introduced in Comparative Examples 1 and 3, the diameter of the antibacterial circle measured is reduced, indicating that the positively charged amino group can contact the negatively charged bacterial cell membrane through electrostatic interaction, thereby destroying the stability and integrity of the cell membrane and having an antibacterial effect. Nano titanium dioxide is not added in Comparative Example 2, indicating that the addition of nano titanium dioxide can have an antibacterial effect, which may be due to the fact that bacteria produce harmful substances such as hydrogen peroxide and superoxide ions while producing metabolites. Nano titanium dioxide can inhibit the production of harmful substances, thereby achieving the effect of inhibiting bacterial cell metabolism.
[0049] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A femoral head prosthesis adapted for multi-taper femoral stem revision, characterized in that: The invention comprises a femoral head prosthesis, which comprises the following raw materials in parts by weight: 40-70 parts of polyetheretherketone and 10-25 parts of composite filler; the composite filler is amination basalt fiber grafted with acyl chloride nano-titanium dioxide, and the amination basalt fiber is basalt fiber grafted with 2-bromoethylamine hydrobromide.
2. The femoral head prosthesis for multi-taper femoral stem revision according to claim 1, characterized in that: The preparation method of the composite filler comprises the following steps: A. Disperse the pretreated basalt fiber in deionized water, add sodium hydroxide solution, stir and mix at room temperature, then add 2-bromoethylamine hydrobromide solution and stir to react for 3-5 hours. After the reaction is completed, wash with deionized water to prepare amino basalt fiber; B. Take nano titanium dioxide and add deionized water, disperse by ultrasonic at room temperature, add sodium chloroacetate and drop sodium hydroxide solution to adjust the pH to 11-13, heat in an oil bath at 100-120° C. for 3-5 hours, cool to room temperature and wash to neutrality, then centrifuge and dry to prepare carboxylated nano titanium dioxide; C. Take carboxylated nano-titanium dioxide and add thionyl chloride, add N,N-dimethylformamide after ultrasonic oscillation, place in an 80-95°C oil bath and stir to react for 18-26 hours, filter, wash and dry to prepare acyl chloride nano-titanium dioxide; D. Take acyl chloride nano-titanium dioxide and add tetrahydrofuran solvent. After ultrasonic dispersion, add amino basalt fiber and triethylamine, stir and mix evenly, place in a 10-30°C water bath and stir to react for 12-24 hours. After the reaction is completed, centrifuge, wash and dry to prepare a composite filler.
3. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: The specific preparation method of the pretreated basalt fiber in step A is: soak the basalt fiber in an acetone solution for 10 to 12 hours, take it out and filter it dry, then put the basalt fiber into a container filled with deionized water to soak and wash, repeat the process for multiple times, filter it out, and then dry it in an oven to prepare the pretreated basalt fiber.
4. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: The concentration of the sodium hydroxide solution in step A is 1.5-2 g / mL.
5. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: In the step A, the addition ratio of the pretreated basalt fiber, deionized water, sodium hydroxide solution and 2-bromoethylamine hydrobromide solution is 0.2 g: 10-20 mL: 10-20 mL: 15-50 mL.
6. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: In step B, the mass ratio of nano titanium dioxide to sodium chloroacetate is 1:1.2-1.
5.
7. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: In the step C, the addition ratio of carboxylated nano-titanium dioxide and thionyl chloride is 1 g: 60-90 mL.
8. The femoral head prosthesis for multi-taper femoral stem revision according to claim 2, characterized in that: In the step D, the mass ratio of acyl chloride nano-titanium dioxide, amination basalt fiber and triethylamine is 1:0.6-2:0.02-0.
15.
9. The femoral head prosthesis for multi-taper femoral stem revision according to any one of claims 1 to 8, characterized in that: The preparation method of the femoral head prosthesis comprises: weighing polyetheretherketone and composite filler by weight, premixing them in a high-speed mixer, and then mixing, extruding, granulating and molding them at 280-365° C. using a twin-screw extruder to prepare the femoral head prosthesis.